1995
DOI: 10.3109/00365599509180031
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Primary Malignant Neoplasms in Urologic Patients

Abstract: One hundred and four patients with multiple primary malignant neoplasm (MPN) with at least one genitourinary organ involved were analyzed. The 104 patients represented 0.9% of all cancer patients and 9.0% of all urologic tumor cases. Tumors of the prostate and bladder in urologic cancers and tumors of the gastrointestinal tract, particularly stomach cancer, in non-urologic cancers were predominantly involved. In 79 cases (76.0%), the second tumors were discovered within 5 years from the diagnosis of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…Rabbani et al also reported that the papillary type of RCC is associated with a significantly increased risk of second cancers in the prostate and bladder 13 . Other smaller studies have reported that the most common sites for second primary cancers in RCC are the prostate, colon and urinary bladder 22;23 . While second cancers in the bladder accounted for 6.4% of all SPCs in our study (Table 1), the risk was significant only in patients aged 60 years or more (at time of diagnosis of either RCC or the SPC), with RCCs ≤5cm in size and in patients without a history of radiation therapy (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…Rabbani et al also reported that the papillary type of RCC is associated with a significantly increased risk of second cancers in the prostate and bladder 13 . Other smaller studies have reported that the most common sites for second primary cancers in RCC are the prostate, colon and urinary bladder 22;23 . While second cancers in the bladder accounted for 6.4% of all SPCs in our study (Table 1), the risk was significant only in patients aged 60 years or more (at time of diagnosis of either RCC or the SPC), with RCCs ≤5cm in size and in patients without a history of radiation therapy (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…Koyama et al [11] studied 104 patients with multiple primary tumors and found an incidence of multiple tumor occurrences of 9% in patients with primary urologic tumors. He found a predominant occurrence of prostate and bladder cancers in urologic cancers and stomach cancer in nonurologic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a RCC have a significantly higher risk of other subsequent primary malignancies [6,24]. While prevalence studies based on autopsy series have identified a 30% to 40% incidence of other primary malignancies in RCC patients, cohort studies have identified rates of 4.5 to 27.4% [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…While prevalence studies based on autopsy series have identified a 30% to 40% incidence of other primary malignancies in RCC patients, cohort studies have identified rates of 4.5 to 27.4% [6,7]. A study by Czene et al clearly indicates that patients with RCC are at increased risk of other cancers not only the first year after primary diagnosis, but also after more than 10 years [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation